Possibility of E-instructional Design and Development of a Distance Education Context in Vocational Consultancy - Dincyurek, Sibel (Kamla-Raj Enterprises, 2016)
The developments that have arisen in education settings today has led to a change in the design of the curricula. Today, societies have also changed over the time, resulting in a need for additional support. The aim of this paper is to evaluate the certificate program of career counselling based on distance education at Eastern Mediterranean University (EMU). It is considered that developing the spatial ability of students, who are currently in 12th grade and are, preparing for university, will result in supporting them both in their daily lives and professional environments. The importance and necessity of understanding, grasping and using the relations between concepts of space, plane, point, line and dimension are emphasized. The study conducted in this paper has attempted to define which concept model learners have for words like space, plane and dimension. A case study was employed in this research paper, focusing on a case in order to clarify the situation.
Keywords: ADDIE; Career Counseling; Constructivist Thinking; Online Certificate Programs; Web-based Learning